1998
DOI: 10.3109/03008209809002435
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Hyaluronan and Dermatan/Chondroitin Sulfate Proteoglycans in Human Aortic Dissection

Abstract: Aortic dissections (AD) are characterized by the separation of the artery into two sheets, possibly due to fragility of the vessel wall. A mucoid histological pattern, imparted to the tissues mainly by hyaluronan and proteoglycans, can be seen in "cysts" and, in chronic cases, in a band of repair tissue. We studied the localization of hyaluronan, versican, decorin and biglycan in situ in aortas of 21 patients with recent AD, 8 with chronic AD and in 15 control cases. None of these substances was increased in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…In view of its histochemical characteristics, this mucoid material most likely corresponds to intact or modified large glycosaminoglycans. These either form part of PG molecules, in which they constitute lateral chains of a protein core, or exist in isolation, such as hyaluronan [18]. Several studies [11][12][13]17] have dealt with the role of metalloproteinases in nonatheromatous aortic diseases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In view of its histochemical characteristics, this mucoid material most likely corresponds to intact or modified large glycosaminoglycans. These either form part of PG molecules, in which they constitute lateral chains of a protein core, or exist in isolation, such as hyaluronan [18]. Several studies [11][12][13]17] have dealt with the role of metalloproteinases in nonatheromatous aortic diseases.…”
Section: Discussionmentioning
confidence: 98%
“…However, the relationship of MMPs to the areas of mucoid degeneration has never been explored. Although these areas, which are proteoglycan (PG)-rich, are common features in AscAA/AD [11], the exact nature [18] and the involvement of the molecules retained in these anionic regions are still unknown. Recently, we showed that thrombin, which has an affinity for sulfated glycosaminoglycans, could be retained within these areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…Slavin e col propuseram como causa a mediólise segmentar idiopática na qual se observa processo degenerativo da camada média (degeneração medial ou mediólise), caracterizado pela fragmentação do tecido elástico com formação de pequenos espaços preenchidos por tecido colágeno 2,12,13,14 . Esta alteração também é comumente encontrada nas dissecções agudas de aorta e nos aneurismas rotos da aorta abdominal 4 . Os aneurismas que acometem a artéria cólica média geralmente são assintomáticos, mas tornam-se graves em situação de rotura, trombose e embolização distal 2,8,9 .…”
Section: Discussionunclassified
“…Considering that the extracellular matrix (ECM) constitutes a great part of the arterial wall, and that it plays a pivotal role in the biomechanical properties of virtually every organ, it is probable that lesions of this compartment are involved in AscAA/AD. As mentioned above, alterations in mucoid content (probably proteoglycans) and in the elastic system have been described [6]. We previously showed by morphometry that in both diseases collagen is decreased [7] throughout the media in AscAA and mostly in the external portion of this layer (where the cleavage occurs) in AD.…”
Section: Introductionmentioning
confidence: 99%